2011
DOI: 10.1002/adma.201102938
|View full text |Cite
|
Sign up to set email alerts
|

Diisopropylammonium Chloride: A Ferroelectric Organic Salt with a High Phase Transition Temperature and Practical Utilization Level of Spontaneous Polarization

Abstract: A simple organic salt, diisopropylammonium chloride, shows the highest ferroelectric phase transition temperature among molecule-based ferroelectrics with a large spontaneous polarization, making it a candidate for practical technological applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
174
0
9

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 322 publications
(197 citation statements)
references
References 31 publications
14
174
0
9
Order By: Relevance
“…For example, while both BTO and P(VDF-TrFE) maintain stable ferroelectricity up to approximately 130°C, BTO has a higher spontaneous polarization, 26 μC cm−2 versus 8 μC cm−2, and a lower coercive field, 10 kV cm−1 versus 500 kV cm−1 [7,21]. Recently, Fu et al reported the synthesis and ferroelectric properties of solution-processed organic ferroelectric crystals known as diisopropylammonium chloride (DIPAC) [33] and diisopropylammonium bromide (DIPAB) [34], with a remarkably lower coercive field and high polarization, comparable to that of conventional inorganic ferroelectrics such as BTO. In the case of DIPAC, the spontaneous polarization is 8.9 μC cm −2 and the coercive field is 9 kV cm −1 , while for DIPAB the spontaneous polarization is 23 μC cm −2 with a coercive field of 5 kV cm −1 , approximately the same as BTO.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, while both BTO and P(VDF-TrFE) maintain stable ferroelectricity up to approximately 130°C, BTO has a higher spontaneous polarization, 26 μC cm−2 versus 8 μC cm−2, and a lower coercive field, 10 kV cm−1 versus 500 kV cm−1 [7,21]. Recently, Fu et al reported the synthesis and ferroelectric properties of solution-processed organic ferroelectric crystals known as diisopropylammonium chloride (DIPAC) [33] and diisopropylammonium bromide (DIPAB) [34], with a remarkably lower coercive field and high polarization, comparable to that of conventional inorganic ferroelectrics such as BTO. In the case of DIPAC, the spontaneous polarization is 8.9 μC cm −2 and the coercive field is 9 kV cm −1 , while for DIPAB the spontaneous polarization is 23 μC cm −2 with a coercive field of 5 kV cm −1 , approximately the same as BTO.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular ferroelectrics, on the other hand, readily grow into large single crystals and afford greater synthetic flexibility than polymers, while avoiding many of the difficulties presented by oxides. For these and other reasons, there has been renewed interest in the development of new high-performance molecular ferroelectrics [12][13][14][31][32][33][34][35]. Some of the key properties of useful ferroelectrics are high spontaneous polarization, a transition temperature well above room temperature, and a low coercive field [7].…”
Section: Introductionmentioning
confidence: 99%
“…3 However, they typically suffer from low spontaneous polarization, low transition temperature, and weak piezoelectric properties even at low temperatures. Recent results on croconic acid 4 and disopropylammonium chloride (bromide) 5,6 have been indeed a breakthrough due to a combination of high enough transition temperature and polarization combined with low coercive field and switchability. These discoveries paved the way for using organic ferroelectrics in bioelectronics, biosensing, harvesting systems, MEMS, just to name a few.…”
mentioning
confidence: 99%
“…Tip-induced domain structures and polarization switching in ferroelectric amino acid glycine E. Seyedhosseini, 1,a) I. Bdikin, 2 M. Ivanov, 1 D. Vasileva, 3 A. Kudryavtsev, 4 B. J. Rodriguez, 5 and A. L. Kholkin 1,3 (Received 3 December 2014; accepted 24 March 2015; published online 19 August 2015) Bioorganic ferroelectrics and piezoelectrics are becoming increasingly important in view of their intrinsic compatibility with biological environment and biofunctionality combined with strong piezoelectric effect and a switchable polarization at room temperature. Here, we study tip-induced domain structures and polarization switching in the smallest amino acid b-glycine, representing a broad class of non-centrosymmetric amino acids.…”
mentioning
confidence: 99%
“…• Screen printable thick-films based upon piezoceramic powders [78] and composites such as polyvinylidene-trifluoroethylene-PZT (PVDF-TrFE) [79] • Organic crystals: single-crystal diisopropylammonium chloride (DIPAC) and diisopropylammonium bromide (DIPAB) [80,81] MEMS devices require thin and thick film technologies since the layers of the materials must be below 100 µm. Thin-film technologies, physical or chemical deposition, are used to fabricate films with thickness lower than 5 µm.…”
Section: Piezoelectric Materialsmentioning
confidence: 99%